Northern agriculture: constraints and responses to global climate change - Mela, Timo (Agricultural Research Centre of Finland, 1996)
Pohjoisella havumetsävyöhykkeellä auringon säteilyenergian vuotuinen määrä jää vähäiseksi säteilyn pienen saapumiskulman takia. Maataloutta harjoitetaan tällä alueella äärirajoillaan, sillä ilmaston kylmyys (matalat lämpötilat, lyhyt kasvukausi, hallat kasvukauden aikana, pitkät ja kylmät talvet sekä paksu lumipeite) rajoittavat viljelyä. Suomessa kasvukauden pituus vaihtelee etelän 180 päivästä pohjoisen 120 päivään. Tämän vuoksi viljelykasvien kasvuajan on oltava lyhyt, mikä rajoittaa niiden kykyä tuottaa suuria satoja. Maatalous on edistyneintä alueen eteläosissa Pohjois-Euroopassa, Keski-Siperiassa ja Kanadan preerioilla ns. hemiboreaalisella kasvimaantieteellisellä alueella, missä kasvukauden tehoisan lämpötilan summa on korkeampi kuin 1200 °C. Viljelyolosuhteet heikkenevät pohjoiseen päin ilmaston kylmetessä, ja viljan viljely muuttuu karjataloudeksi. Pohjois-Euroopassa maata viljellään aina napapiirille (66°N) saakka. Pohjois-Amerikassa pellot ulottuvat suunnilleen leveysasteelle 55°N, Aasiassa muutamin paikoin leveysasteelle 60°N. Suomi on maailman pohjoisin maa, jossa koko peltoala, 2,5 miljoonaa hehtaaria, sijaitsee leveysasteen 60°N pohjoispuolella. Ilmaston ja ilmakehän hiilidioksidipitoisuuden ennustettu muutos vaikuttavat todennäköisesti voimakkaasti kasvuoloihin näillä pohjoisilla alueilla, missä vuotuinen keskilämpötila on 5 °C tai vähemmän. Vaikutukset ovat joko edullisia tai epäedullisia.

In the northern circumpolar zone, the area between the 600°Cd and 1200°Cd isopleths of effective temperature sum above 5°C, the annual receipt of solar energy is limited by the low angle of radiation arriving at the earth's surface. This is the primary cause of the climatic constraints observed in the zone, such as low temperatures, a short growing season, frosts during the growing season, long and cold winters and thick snow cover. In Finland, the length of the growing season varies from 180 days in the south (60°N) to 120 days in the north (70°N). Consequently, the growing time for crops from sowing to ripening is also short, which limits their ability to produce high yields. The most advanced forms of farming in the high-latitude zone are encountered towards the south in Northern Europe, central Siberia and the prairies of Canada, i.e. mainly in the phytogeographical hemiboreal zone where the effective temperature sum is higher than 1200°Cd. Conditions for agriculture then deteriorate gradually further north with the cooling of the climate, and this is reflected as an increase in cattle rearing at the expense of grain cultivation. In northern Europe farming is practised as far north as to the Arctic Circle, at about W°N latitude. In North America, fields extend to about 55°N In Asia, there are few fields north of 60°N Finland is the most northern agricultural country in the world, with all its field area, about 2.5 million hectares, located north of latitude 60°N Changes in the climate and atmospheric CO2 predicted for the future are likely to have a strong influe nce, either beneficial or disadvantageous, on the conditions for growth in northern areas where the annual mean temperature is 5°C or less.
Keywords: Suomi; ilmasto; kasvukausi; lämpösumma; talvivauriot; Finland; circumpolar zone; crop production; growth conditions; growing season; solar radiation; temperature sum; winter damage